-5+6 = 1. This is the answer. Thank you
Answer:
Use m athway
Step-by-step explanation:
Answer:
69
Step-by-step explanation:
m1 = 180 - (180 - 39 - 30) = 180 - 111 = 69
Answer: x - 5/x + 1
Step-by-step explanation:
This algebraic fraction
The task to be performed here is factorisation and simplification. Now going by the question,
x² + 4x - 45/x² + 10x + 9, the factorisation of
x² + 4x - 45 = x² + 9x - 5x - 45
= x(x + 9 ) - 5(x + 9 )
= ( x + 9 )(x - 5 ), don't forget this is the algebraic fraction's Numerator
The second part
x² + 10x + 9 = x² + x + 9x + 9
= x(x + 1) + 9( x + 1 )
= ( x + 9 )( x + 1 ), this is the algebraic denominator.
Now place the second expression which is the denominator under the first expression which is the numerator.
( x + 9 )( x - 5 )/( x + 9 )( x + 1 ).
You can see that, ( x + 9 )/( x + 9 ) divide each other , therefore therr then cancelled and left with
x - 5/x + 1
Answer:
x = 14/9
Step-by-step explanation:
70 - 8x = 56 + x
- 8x - x = 56 - 70
- 9x = - 14
- x = - 14/9
x = 14/9